Future telecommunications : - Heldman, Robert K. (McGraw-Hill, 1993)
The aim of this book, Future of the Telecommunications Industry: Forecasting and Demand Analysis, is to describe leading research in the area of empirical telecommunications demand analysis and forecasting in the light of tremendous market and regulatory changes. Its purpose is to educate the reader about how traditional analytic techniques can be used to assess new telecommunications products and how new analytic techniques can better address existing products. The research presented focuses on new products such as Internet access and additional lines and new techniques such as hazard modeling, adaptive forecasting and neural networks. The scope of this volume includes new telecommunications products, new analytical techniques, and a review of market changes in the US and other countries. Some of the most critical questions facing the industry are addressed here, such as the impact of competition, customer churn, rate re-balancing, and early assessment of new products. The research includes a variety of different countries, products and analytic tools.